Boosting knowledge, attitudes, and practices: An experimental controlled study evaluating the effectiveness of m-health training on antimicrobial resistance for hemodialysis nurses - Hossam Alhawatmeh; Mohammed Aljarrah; Issa M Hweidi; Nezam Al-Nsair; Mohammad S Alyahya; Sawsan Abuhammad (SAGE Open Medicine)
Aim/Objective: To evaluate the impact of an m-health training program on nurses’ knowledge, attitudes, and practices concerning antimicrobial resistance within hemodialysis units. Background: Hemodialysis patients face high infection risks, driving antimicrobial use and resistance. Nurses’ antimicrobial resistance knowledge gaps underscore the need for effective training. Design: A parallel group randomized controlled trial. Methods: A convenience sample of 64 nurses was cluster-randomized into either an m-health group ( n = 32) or a control group ( n = 32). The m-health group received antimicrobial resistance education through a WhatsApp Chatbot, while the control group received no information on the study topic. However, they were provided the study intervention after the evaluation was completed. The nurses’ knowledge, attitudes, and practices regarding antimicrobial resistance were assessed with self-developed instruments at three time points: Baseline (Time 1), immediately after the intervention (Time 2), and 1 month later (Time 3). Results: Repeated-measures Analysis of Variance (ANOVA) (within-subject) tests indicated significant differences in mean scores for antimicrobial resistance knowledge, attitudes, and practices across the three time points in the m-health group. The repeated-measures ANOVA (mixed model) tests revealed significant interaction effects in antimicrobial resistance knowledge, attitudes, and practice. Conclusions: m-Health training program significantly enhanced dialysis nurses’ knowledge, attitudes, and practice toward antimicrobial resistance. It is recommended to communicate the findings of this study to managers and policymakers to equip them with the information needed to develop and implement effective strategies, policies, and multidisciplinary interventions aimed at reducing antimicrobial resistance in hemodialysis units.